Sitting Posture Recognition based on data fusion on pressure cushion - Junrong Bao; Wenfeng Li; Jian Li; Yanhong Ge; Chongzhi Bao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Sitting postures affect their safety in wheelchair for persons with the disability or the elder people. In this paper, we built the body pressure collection system; it is explored the relationship between the pressure distributions and sitting posture; based on daily sitting posture of disabled and older people , the eight states is summarized that people sit on the wheelchair, and using density-based clustering methods establish the evaluation model of difference sitting postures. The instances verify that the model can accurately predict the relations between pressure distribution and sitting postures. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2329